PENGARUH AUDIT TENURE, FIRM SIZE, KEPEMILIKAN PUBLIK, DAN KOMPLEKSITAS OPERASI TERHADAP AUDIT DELAY: AUDIT DELAY - Amanda Priscilia; Yunita Kurnia Shanti (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to examine the effect of audit tenure, firm size, public ownership, and operational complexity on audit delay. The research employs a quantitative approach using secondary data obtained from the annual report of consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2020-2024. The population of this study consisted of 164 companies. The sample was selected using a purposive sampling methode, resulting in 50 companies that met the predetermined criteria. With an observation period of five years, the study obtained a total of 250 observations. The data ware analyzed using panel data regression with the assistance of EViews 12 software. The result indicate that audit tenure, firm size, public ownership, and operational complexity simultaneously affect audit delay. Partially, audit tenure dan public ownership have a significant effect on audit delay. Meanwhile, firm size and operational complexity do not have a significant effect on audit delay. Keywords: Audit tenure, Firm size, Public Ownership, Operational Complexity, Audit delay